Digital Infrastructure Readiness in Supporting National Telehealth Services: A Comprehensive Review - Abimulyani, Yumi; Kaluku, Suratno (Oshada, 2025)
The readiness of digital infrastructure is crucial for supporting effective national telehealth services, particularly in developing countries and remote areas. This comprehensive review examines the key factors influencing digital infrastructure readiness, including policy and regulation, connectivity and devices, digital competency and literacy, and equity of access. Through a systematic literature review of 21 scholarly publications from 2020 to 2025, this study identifies critical challenges in telehealth implementation, including infrastructure limitations, lack of trained human resources, regulatory barriers, and digital divides. The findings reveal that successful national telehealth implementation depends heavily on robust digital infrastructure, supportive policies, digital literacy, and equitable access. This research recommends strategic investments in infrastructure development, human resource training, adaptive policies, and inclusive technological solutions to ensure telehealth can truly expand access and improve healthcare service quality. The study contributes to both theoretical understanding and practical implementation of telehealth systems in resource-constrained settings